2017
DOI: 10.1590/0004-282x20160194
|View full text |Cite
|
Sign up to set email alerts
|

Experimental neurocysticercosis: absence of IL-4 induces lower encephalitis

Abstract: Neurocysticercosis (NCC) is the most severe clinical manifestation of cysticercosis. One of the factors responsible for its symptomatology is the host inflammatory response. Therefore the influence of interleukin 4 (IL-4) on the induction of encephalitis in experimental NCC was evaluated. Methods BALB/c (WT) and BALB/c (IL-4-KO) mice were inoculated intracranially with Taenia crassiceps cysticerci and euthanized at 7, 30, 60 and 90 days later, the encephala removed and histopathologically analyzed. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 168 In their study, Silva et al found that IL-4 knockout mice with experimentally induced neurocysticercosis had lower cerebral edema, lower inflammatory infiltrates and prolonged survival of the parasites in the brain. 169 This indicates that IL-4 is preferentially expressed in response to infections in an attempt to reduce brain damage, possibly explaining the previous observations that asymptomatic patients from endemic areas exhibit increased production of IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 59%
“… 168 In their study, Silva et al found that IL-4 knockout mice with experimentally induced neurocysticercosis had lower cerebral edema, lower inflammatory infiltrates and prolonged survival of the parasites in the brain. 169 This indicates that IL-4 is preferentially expressed in response to infections in an attempt to reduce brain damage, possibly explaining the previous observations that asymptomatic patients from endemic areas exhibit increased production of IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 59%
“…The role of immunity of the host for protection against neurocysticercosis is very interesting. The observation by Silva et al 2 on interleukin 4 (IL4) and neurocysticercosis is a good example. Here, we would like to draw more attention to a complex immunological defect that can underline increased risk for neurocysticercosis.…”
mentioning
confidence: 99%